Effects of ankle joint injuries on balance in male and female gymnasts - Dallas, G.; Dallas, K. (Science of Gymnastics Journal, 2016)
Gymnastics is a sport where there always exists a real and present danger of physical injury. Athletic injury, whether temporary or permanent, is a painfully disruptive and uncontrollable interruption in a gymnast's career. Injuries can have profound negative consequences on a gymnast`s balance, with lower limbs injuries constituting the majority of these injuries. The purpose of this study was to assess differences in postural stability between high level male and female artistic gymnasts who suffered ankle sprain injuries (ASI) on either or both legs in the past. Ten female (age = 16.66 ± 3.20 years, mass = 47.30 ± 8.00 kg, height = 158.00 ± 5.75 cm) and ten male gymnasts (age = 22.30 ± 1.77 years, mass = 62.00 ± 3.33 kg, height = 168.50 ± 3.03 cm) volunteered to participate in this single visit study. Participants were measured for Limits of Stability variables (Reaction Time [RT]; Center of Gravity Velocity [MVL]; Directional Control [DCL]; End Point Excursion [EPE]; Maximum Excursion [MXE]) to examine the effect of ASI on postural stability. Limits of Stability (LOS) test were used to examine postural stability of gymnasts using the EquiTest Computerized Dynamic Posturography system. Results indicated that females had significantly less ASI than male gymnasts and recorded significantly lower values in Reaction Time and higher values in Movement Velocity during LOS test. In conclusion, the number of past ASI influence postural control as the musculo-tendinous changes around the ankle lead to a reduction of proprioceptive information and may contribute to the deficient postural control mechanisms after injury. Furthermore, postural control may be affected even after acute ASI resolution